Financial impacts of innovation in Six Sigma projects - Oprime, Pedro Carlos; Pimenta, Marcio Lopes; Jugend, Daniel [UNESP]; Andersson, Roy (Routledge Journals, Taylor & Francis Ltd, 2019)
The purpose of this paper is to present empirical evidence about the relationship between the characteristics of Six Sigma projects, as drivers of innovation, and financial performance at organisational and operational levels. The findings were obtained through the analysis of 83 projects of a big automobile corporation, carried out in its industrial plants operating in North America, Europe, and South America. Statistical treatments were performed to analyse the occurrence of several project characteristics, such as areas focus, innovativeness of change, tools used, and average duration of the project. There was an indication that longer Six Sigma projects that involve more people are those that produce the best financial results. Statistical evidence was obtained to affirm that Six Sigma enhances the capacity to address incremental innovation, and that the adoption of Six Sigma impacts directly on financial performance. There is no statistical evidence that Six Sigma enhances the capacity to address radical innovation and that the number of tools used affects the project's financial result. Most of the projects studied presented basically incremental innovations; however, radical projects have a greater financial impact when applied to the design and redesign of new products and processes.
Keywords: financial impacts; innovation; quality management; Six Sigma